Tumor‐associated macrophages regulate the function of cytotoxic T lymphocyte through PD‐1/PD‐L1 pathway in multiple myeloma. (20th May 2022) - Zhang, Jiangbo; Liu, Zhaoyun; Cao, Panpan; Wang, Hao; Liu, Hui; Hua, Luoming; Xue, Hua; Fu, Rong
Abstract: Background: Tumor‐associated macrophages (TAMs) are originated from circulating mononuclear cells in peripheral blood. They result from the recruitment of tumor cells and are a vital constituent of the tumor microenvironment. TAMs may be involved in the immunological escape of vicious clonal plasma cells (PC) in the bone marrow (BM) of sufferers with myeloma. Methods: From March 2020 to January 2021, 28 healthy controls (HC) and 86 multiple myeloma (MM) (53 newly diagnosed MM [NDMM] and 33 remissions) patients were enrolled as objects of the study. The expression of TAMs in the BM, CSF1 on CD138 + cells, and CSF1R on macrophages were detected by the method of flow cytometry, and the expression of PD‐1 on CD8 + T cells and PD‐L1 on TAMs were also done. Bone marrow mononuclear cells (BMMNCs) were extracted and cultured into TAMs, CD8 + T cells were sorted by magnetic beads and cultured, a coculture system was established and different inhibitors were added. The expression of the perforin and granzyme B was detected by flow cytometry. Results: The percentage of TAMs in NDMM group (61.49 ± 2.176%) increased when compared with remission (23.08 ± 1.699%, p  < 0.001) and HC group (17.95 ± 1.865%, p  < 0.001), and TAMs decreased after adding CSF1R inhibitor. Moreover, the expression of CSF1 on CD138 + cells increased significantly in NDMM group (17.090 ± 0.9156%) than remission (8.214 ± 0.5911% p  < 0.001), and HC group (5.257 ± 0.6231%, p  < 0.001), and CSF1R on macrophages increased significantly in NDMM group (58.78 ± 2.286%) than remission (20.74 ± 1.376%, p  < 0.001) and HC group (17.42 ± 1.081%, p  < 0.001). The expression of PD‐1 on CD8 + T cells in NDMM group (32.64 ± 2.982%) increased than remission (20.35 ± 2.335% p  < 0.01) and HC group (17.53 ± 1.349%, p  < 0.001), and PD‐L1 on TAMs also increased in NDMM group (50.92 ± 2.554%) than remission (20.02 ± 1.893%, p  < 0.001) and HC group (13.08 ± 1.289%, p  < 0.001). When CD8 + T cells were cocultured with TAMs, the perforin and granzyme B levels decreased significantly. However, the perforin and granzyme B levels were partly restored after adding CSF1R inhibitor and anti‐PD‐L1 antibody. Conclusion: Our study shows that TAMs were increased in MM patients which can inhibit the function of cytotoxic T lymphocyte (CTL) through the PD‐1/ PD‐L1 signaling pathway and participate in the occurrence of immune escape of myeloma cells. Abstract : Tumor‐associated macrophages(TAMs) are a vital constituent of the tumor microenvironment and involved in the immunological escape of vicious clonal plasma cells of myeloma patients. Our research shows that CSF1R can regulates the production of TAMs while the PD‐1/PD‐L1 pathway regulates the effect of TAMs on cytotoxic T lymphocyte. It may provide a new basis for targeted therapy of multiple myeloma.